Psychometric properties of an Arabic translation of the external and internal shame scale (EISS) - Feten Fekih-Romdhane; Diana Malaeb; Mariam Dabbous; Rabih Hallit; Sahar Obeid; Souheil Hallit (BMC Psychiatry, 2023)
Abstract Background The concept of shame in Arab societies displays multiple differences when compared to Western societies in terms of nature, sources, types, and correlates. Surprisingly, we could not find any study investigating this increasingly important construct in Arab countries or the broad Arabic-speaking communities. This may likely be due to the lack of valid instruments assessing shame in the Arabic language. To address this major gap and contribute to the international literature, we sought to examine the psychometric properties of an Arabic translation of the External and Internal Shame Scale (EISS) among a community sample of Arabic-speaking adults from Lebanon. Methods An online survey was conducted among Lebanese adults between July and August 2022. A total of 570 Lebanese adults completed the EISS, as well as Depression Anxiety Stress Scales, Other as shamer scale, and the Standardized Stigmatization Questionnaire. Exploratory-to-confirmatory (EFA-CFA) factor analyses were conducted. Results Exploratory and confirmatory factor analyses supported a unidimensional model of EISS scores, with all eight items retained. Scores achieved scalar invariance across gender, with no significant difference reported between females and males. EISS scores were found to have adequate composite reliability (McDonald’s ω = 0.88 for the total score); as well as adequate patterns of correlations with depression, anxiety and stress symptoms, as well as stigmatization scores. Finally, our analyses provide support to the concurrent validity of the Arabic version of the scale, by showing that the EISS total scores strongly correlated with the external shame measure “other as shamer”. Conclusion Although further validations are necessary before our findings could be generalized, we preliminarily suggest that this is a short, easy-to-use, self-report scale that enables a reliable and valid measure of the shame construct among Arabic-speaking people.